ANALISIS KEPUASAN PELANGGAN BERBELANJA DI BUDIMAN SWALAYAN KOTA PADANG - Putri, Sinta Rahma; Kartikowati, Sri; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to identify and analyze the level of customersatisfaction from service dimensions and to figure out attributes needed to be improvedto increase customers satisfaction. This research was conducted at BudimanSupermarkets Padang. The population is all customers of Budiman Supermarkets. Thesamples is 100 customers determined byaccendential sampling technique. Data analysistechnique is used by Importance Performance Analysis (IPA) and Customer SatisfactionIndex (CSI). The results of Customer Satisfaction Index shows that customers aresatisfied with the services provided by Budiman Supermarket; and the results ofImportance Performance Analysis indicates some attributes need to be improved:Quadrant A consisted of K1, K2, K3, DT, DT2, DT3, BL3; and Quadrant B consisted ofK4, K5, J1.Keywords:Service, Customer Satisfaction